Preparation of Orange Peel Based Activated Carbons Using Chemical Activation and Surface Modification Method as Electrode's Materials for Lithium Ion Capacitor - Arie, Arenst Andreas; Kristianto, Hans; Martin, Halim; Lee, Joong Kee (AMER SCIENTIFIC PUBLISHERS, 2018)
In this work, activated carbons (AC) were initially prepared from orange peel by a chemical activation process using ZnCl2. It was then followed by the surface modification method using HNO3. The surface modified activated carbons were then used as electrode materials for Li-ion capacitor applications. The specific surface area of similar to 1200 m(2)g(-1) was obtained for the material treated with a 1: 2 ratio of ZnCl2 to orange peel. A Li-ion Capacitor (LIC) was fabricated with orange peel based AC electrodes, and the Cyclic Voltammetry (CV) results showed an initial specific capacitance of 66 F g(-1) at scan rate of 0.1 mV s(-1). An improved capacitor property with an initial specific capacitance of 100 F g(-1) was shown by the AC electrodes after the surface modification process using HNO3. However the surface area of surface modified AC was lower than that of unmodified AC. This result revealed that the orange peel derived AC can be used effectively as a promising electrode material to construct LIC type supercapacitors.